5-hydroxymethyl-2-furaldehyde purified from Japanese pear (Pyrus pyrifolia Nakai cv. Nijisseiki) juice concentrate inhibits melanogenesis in B16 mouse melanoma cells. Issue 11 (1st November 2020) - Bito, Tomohiro; Koseki, Kyohei; Asano, Ryota; Ueda, Nakaba; Yamada, Takuhiro; Yabuta, Yukinori; Ichiyanagi, Tsuyoshi; Ishihara, Atsushi; Watanabe, Kishi; Watanabe, Fumio
ABSTRACT: Pear juice concentrate prepared by boiling Japanese pear ( Pyrus pyrifolia Nakai cv. Nijisseiki) juice can significantly inhibit the activity of tyrosinase, a key enzyme in melanin synthesis in human skin. Using the ethanol extract of pear juice concentrate, we homogeneously purified an active compound that was identified as 5-hydroxymethyl-2-furaldehyde (5-HMF) through 1 H- and 13 C-NMR and mass spectroscopy. We observed that 5-HMF inhibited the monophenolase and diphenolase activities of mushroom tyrosinase as a mixed-type inhibitor ( K i values of 3.81 and 3.70 mmol/L, respectively). In B16 mouse melanoma cells, treatment with 170 µmol/L of 5-HMF significantly reduced α-melanocyte-stimulated melanin synthesis by suppressing the cyclic adenosine monophosphate-dependent signaling pathway involved in melanogenesis. The results of our study indicated that 5-HMF can be potentially used as a skin-lightening agent in the cosmetic industry. Abbreviations: AC: adenylate cyclase; CREB: cAMP response element-binding protein; dhFAME: S-(−)-10, 11-Dihydroxyfarnesoic acid methyl ester; DMEM: dulbecco′s modified eagle medium; l -DOPA: 3-(3, 4-Dihydroxyphenyl)- l -alanine; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; HEPES: 4-(2-Hydroxyethyl)-1-piperazine ethane sulfonic acid; 5-HMF: 5-Hydroxymethyl-2-furaldehyde; MITF: microphthalmia-associated transcription factor; α-MSH: α-Melanocyte-stimulating hormone; PKA: protein kinase A; PVDF: polyvinylidene difluoride; SDS: sodium dodecyl sulfate; TRP1: tyrosinase-related protein 1; TRP2: tyrosinase-related protein 2 Graphical abstract: uf0001 5-Hydroxymethyl-2-furaldehyde can act as a tyrosinase and/or melanogenesis inhibitor, which can be used as a skin-lightening agent in the cosmetic industry.